O uso agressivo da linguagem: um estudo discursivo-interacionista da impolidez nos comentários da internet - Wilma Maria Pereira (2022)
Considering online comments as a genre of controversial potential that favors the emergence of impolite acts—as it generally presents antagonistic points of view—, this paper aims to assess the potentiality of the Modular Approach to Discourse Analysis, which, combined with Culpeper's propositions, may become a significant alternative when studying impoliteness in this discursive modality. Underlying the objective of this study is the notion that impoliteness is a relevant social phenomenon for understanding how individuals relate to each other and, consequently, how human interactions are established in the digital environment. After acknowledging its relevance, our initial hypothesis is that impoliteness can be systematically investigated using the Modular Approach to Discourse Analysis. We consider it suitable for carrying out our proposed research since it offers a theoretical and methodological device that enables extracting simple information systems, which, when combined into complex forms of organization, allows for a more comprehensive investigation of the whole discursive constitution process. When approaching Culpeper's model—which offers relevant descriptive categories to study impoliteness—, it is possible to better explain the impact that constitutive elements of the several discourse dimensions may have on how interactants act and react to defend/attack their faces in interaction. Our object of investigation are impolite comments published on the news website G1 about the political context. Specifically, this study seeks to analyze how situational and textual composition aspects can be strategically handled as devices for promoting impoliteness. We seek to demonstrate how discursive resources, ascertained during the modular analysis, can be used by interactants in the impolite management of relationships between faces, places, and territories. To do so, the research will highlight not only impoliteness strategies, as proposed by Culpeper, but also the elements resulting from the study of the situational and hierarchical dimensions and the forms of relational, enunciative, polyphonic, and strategic organization which are used to promote impoliteness and the management of faces in interaction.